Neurosphere Based Differentiation of Human iPSC Improves Astrocyte Differentiation. (21st December 2015) - Zhou, Shuling; Szczesna, Karolina; Ochalek, Anna; Kobolák, Julianna; Varga, Eszter; Nemes, Csilla; Chandrasekaran, Abinaya; Rasmussen, Mikkel; Cirera, Susanna; Hyttel, Poul; Dinnyés, András; Freude, Kristine K.; et al.
Abstract : Neural progenitor cells (NPCs) derived from human induced pluripotent stem cells (iPSCs) are traditionally maintained and proliferated utilizing two-dimensional (2D) adherent monolayer culture systems. However, NPCs cultured using this system hardly reflect the intrinsic spatial development of brain tissue. In this study, we determined that culturing iPSC-derived NPCs as three-dimensional (3D) floating neurospheres resulted in increased expression of the neural progenitor cell (NPC) markers, PAX6 and NESTIN . Expansion of NPCs in 3D culture methods also resulted in a more homogenous PAX6 expression when compared to 2D culture methods. Furthermore, the 3D propagation method for NPCs resulted in a significant higher expression of the astrocyte markers GFAP and aquaporin 4 ( AQP4 ) in the differentiated cells. Thus, our 3D propagation method could constitute a useful tool to promote NPC homogeneity and also to increase the differentiation potential of iPSC towards astrocytes.